Returns-Chasing Behavior, Mutual Funds, and Beta's Death - Karceski, Jason (Journal of Financial and Quantitative Analysis, 2002)
I develop an agency model where returns-chasing behavior by mutual fund investors causes beta not to be priced to the degree predicted by the standard CAPM. Mutual fund investors chase returns through time, precipitating unusually large aggregate cash inflows into mutual funds just after dramatic market runups. Mutual fund investors also chase returns cross-sectionally across funds so that the highest-performing funds capture the largest fraction of the aggregate inflows into the mutu al fund sector. The interaction of these two flow-performance relationships induces an asymmetry in payoffs to mutual funds where fund managers care most about outperforming peers during bull markets. Since high-beta stocks tend to outperform in up markets, active fund managers tilt their portfolios toward high-beta stocks, reducing the beta risk premium in equilibrium. To support the model's time-series flow-performance assumption, I show empirically that market returns have a large economic impact on subsequent aggregate mutual fund flows. In addition, data on mutual fund holdings suggest that the aggregate stock portfolio held by equity funds is overweighted in high-beta stocks relative to the overall market, though this does not include the cash held by mutual funds. Fama-MacBeth tests indicate that the equity premium falls only slightly as the relative size of mutual funds increases, and the relation is not statistically significant.